Periodic and the Educational Paradigm of Ibnu Sina - Abdullah Muwaffaq (PT ARRUS Intelektual Indonesia, 2022)
Avicenna is one of the figures who has made a major contribution to the body of knowledge in Islam, especially about Islamic education. This paper discusses the educational paradigm of Ibn Sina. In general, education is an appropriate and strategic means and effort to save human life from any matter. The synthesis of Ibn Sina's thought that